2018
DOI: 10.18805/ijar.b-3484
|View full text |Cite
|
Sign up to set email alerts
|

Blood biochemical and hormonal profiles vis-a-vis production performance of single and twin kid bearing Surti goats (Capra hircus)

Abstract: Study was undertaken to investigate the effect of single and twin kidding on blood bio-chemical, hormonal profiles and production performance of 14 goats. The animals were divided into group1 (single kid, n=7) and group 2 (twin kids, n= 7). The blood samples were collected on 0, 7, 15, 30, 45 and 60 day of parturition for analysis of blood profiles. Milk yield and fat% were also recorded on different test days. Serum glucose, albumin, BUN and cholesterol was higher in twin bearing dam; however, it was not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…The overall mean E 2 , P 4 , and cortisol ranges recorded in this study are in accordance with the physiological ranges reported by different authors for clinically healthy nonpregnant, pregnant, and postpartum goats (Gamit et al, 2019;Khan and Ludri, 2002c;Probo et al, 2011;de Souza Castagnino et al, 2015;Tharwat et al, 2013). Nevertheless, some variation might be due to differences in the techniques used (Barth et al, 2018), the experimental model, diet, management, the physiological period, and genotype.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The overall mean E 2 , P 4 , and cortisol ranges recorded in this study are in accordance with the physiological ranges reported by different authors for clinically healthy nonpregnant, pregnant, and postpartum goats (Gamit et al, 2019;Khan and Ludri, 2002c;Probo et al, 2011;de Souza Castagnino et al, 2015;Tharwat et al, 2013). Nevertheless, some variation might be due to differences in the techniques used (Barth et al, 2018), the experimental model, diet, management, the physiological period, and genotype.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found the significantly highest values of both E 2 and P 4 in the whole pregnancy compared with the prior and following periods, consistently with an increased demand for a higher metabolic rate for pregnancy, previously observed in dairy goats (de Souza Castagnino et al, 2015). This trend might happen due to the preparation of the reproductive system for the growth of the uterus and fetus, as previously recorded for goats (Capezzuto et al, 2008;Gamit et al, 2019;Laura et al, 2004). On the other hand, the significant decrease in E 2 and P 4 in early lactation may also reflect a difference in nutrient availability and the related utilization in a catabolic or anabolic manner: this may temporarily change the metabolic requirements to cope with an intensive lactogenesis phase.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Higher level (overall 11.59% or higher) of estrogen was observed in twin pregnancy in Surti goats as compared to single-bearing goat on all test days although it was not significant [ 26 ]. This increase is also physiological, as estrogen is required for uterine contractions during parturition.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, higher blood glucose concentrations at birth than at day 15 postnatal in Surti goat kids and day 28 postnatal in Saanen goat kids have been reported. 40,41 The significantly higher incidence of neonatal hypoglycemia in RSG and SHG kids in the current study suggests a genetic predisposition due to breed differences, which might influence either the ability of the neonatal kids to accumulate energy reserves (glycogen and fatty acids) during gestation or prompt release of accumulated energy reserves immediately after kidding. 9,10,42,43 This could be associated with a variation in the ability of the dams to take up, use, and make dietary nutrients available to the fetus for maintenance and storage during gestation.…”
Section: Discussionmentioning
confidence: 75%